Outdoor education model based on experiential learning in character education for junior high school students - Ahmad Mujahid Yaumul Ridho; Hernawan; Nofi Marlina Siregar (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This research and development was made on the needs of formal school teachers to make it easier to understand and implement the concept of effective experiental learning based learning for informal program design and formal classroom activities related to field experience packaged in the form of games, discussions, simulations and adventures, which are expected to have the impact of the implementation of experiential learning. students move between modes of action, reflection, feelings and thinking. This research design refers to the Research and Development model of ADDIE. Broadly speaking this research is made in 5 stages, namely: Model analysis, Model design, Model development, Model implementation, Model evaluation. The data insturment test collected in this study both at the stage of obtaining basic data and at the trial stage is qualitative data. Therefore the main instrument in this study is the self research. To complete the data and as part of triangulation conducted discussions with expert lecturers, teacher collaborators, outbound instructors and experiental learning activists who are not involved in the research by collecting data using interview guidelines on teachers, questionnaires, questionnaires and observation learning. From the data analysis proved outdoor education model based on experiental learning seems effective to shape the values of character education. Based on the results of research with a model of approach and cohesion in its implementation is very helpful to excite learning, participatory involvement of students, joy and cheerfulness which means the implementation of outdoor learning is not only in the concept, the integration must be really attempted to occur in the learning process.